SISTEM PENGANGKAT BARANG OTOMATIS PADA GUDANG UNTUK MENGHINDARI KERUSAKAN AKIBAT BANJIR - Susila, Tjandra; Sugana, Herin (TESLA Jurnal Teknik Elektro UNTAR, 2008)
In a rainy season, especially in high rain intensity, flood has become a problem to us. It’s called a problem because the impact it caused and it can comes to anyone, anytime at anyplace. When flood comes to our place we usually moved all the important stuff to a safer place to avoid damage to our goods. Especially in a storehouse, where so many production’s materials and maybe machines inside that have to be protected from damage caused by flood. So when flood comes, the workers will move all the important things to a safer or higher place. These activities use all their powers to move those things and it was really wasting time and energy. To save times and energies, we need an automated system to lift or move the production’s materials or the other important stuff when flood comes, so these stuffs are safe from damages.